Doctor Availability and Cost Bearer Influencing Patient Loyalty Mediated by Patient Experience - Fannysa Astika Prihardini; Dini Handayani; MF.Arrozi Adhikara (International Journal of Economics and Management Sciences, 2026)
Patient loyalty is an important indicator of success in healthcare services because it reflects patients’ tendency to reuse healthcare services and recommend them to others. Patient loyalty in healthcare facilities is influenced by various factors, including doctor availability, cost bearer systems, and patient experience during the service process. This study aims to analyze the effect of doctor availability and cost bearer on patient loyalty with patient experience as a mediating variable among patients at the Dental Clinic of Hermina Galaxy Hospital.This research used a quantitative approach with a survey design. Data were collected through questionnaires using a Likert scale from 150 patients at the Dental Clinic of Hermina Galaxy Hospital selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of AMOS software to examine both direct and indirect relationships among the research variables.The results showed that doctor availability and cost bearer have a positive and significant effect on patient experience. Patient experience was also found to have a positive and significant effect on patient loyalty. In addition, doctor availability and cost bearer have a direct influence on patient loyalty and an indirect influence through patient experience as a mediating variable.In conclusion, improving patient loyalty can be achieved by enhancing doctor availability, managing financing systems effectively, and creating positive patient experiences. Hospital management should optimize these factors to improve service quality and maintain patient loyalty